Observations on the geometric design of Saint-Yved at Braine - McClain, Jeoraldean (Zeitschrift für Kunstgeschichte, 1986)
Keywords: braine

A Modern Reconstruction of the West Portals of Saint-Yved at Braine - McClain, Jeoraldean (Gesta, 1985)
In 1832 the west façade of the 12th-century church of the Premonstratensian abbey of Saint-Yved at Braine was demolished. Today the original form of the Gothic west façade is not known because all the documents representing Saint-Yved prior to the demolition of 1832 are either imprecise or incomplete. Nevertheless, modern scholarship has accepted 19th-century reconstructions based on this faulty documentation. In 1971, the site of the demolished façade was excavated and its physical remains were discovered. The excavation proved the necessity of referring to the façade's extant stones, not to 19th-century documents, in order to determine the precise measurements of the church. The following study provides a method whereby the groundplan and the elevation of the old façade of Saint-Yved and its three portals can be reconstructed. The method consists of first measuring the two parts of the façade that are extant: the remains in situ that were excavated in 1971; and the stones of the central Coronation Portal, measured before the portal was rebuilt inside the church in 1970. These dimensions provide a framework for the next step, which is to use architectural elements that exist elsewhere at Saint-Yved to substitute for missing parts of the façade. This method makes use of the fact that solids and voids at Saint-Yved have standardized dimensions which appear throughout the building. Finally, documents which reproduce Saint-Yved prior to the 1832 demolition are used as guides in reconstructing the façade whenever they correspond to actual dimensions of the church.
Keywords: braine

Rediscovered Glass of about 1200 from the Abbey of Saint-Yved at Braine - Caviness, Madeline Harrison (Studies on medieval stained glass : selected papers from the XIth International Colloquium of the Corpus Vitrearum, New York, 1-6 June 1982, 1985)
Keywords: braine

Saint-Yved of Braine: The Primary Sources for Dating the Gothic Church - Caviness, Madeline Harrison (Speculum, 1984)
Keywords: braine

Saint-Yved in Braine und die Anfänge der hochgotischen Architektur in Frankreich - Klein, Bruno (Veröffentlichungen der Abteilung Architektur am Kunsthistorischen Institut der Universität Köln, 1984)
Keywords: braine

St. Yved zu Braine und die mittelalterlichen Nachfolgebauten - Wochnik, Fritz (Analecta Praemonstratensia, 1983)
Keywords: braine

St. Yved zu Braine und die mittelalterlichen Nachfolgebauten - Wochnik, Fritz (Analecta Praemonstratensia, 1982)
Keywords: braine